Bacterial contamination of street-vended spicy puffed-rice sold at Bangladesh Agricultural University campus (Bangladesh Veterinarian, 2015)
This study was undertaken to investigate the bacterial contamination of spicy puffed rice (Jhalmuri) sold by the street vendors at Bangladesh Agricultural University (BAU) campus. Fifteen spicy puffed rice samples were collected from street vendors at the Botanical Garden, Library premises, Riverside, Krishi Bishhobiddaloy (KB) High School and Veterinary Teaching Hospital compound at BAU campus. Microbial quality was assessed by total viable count (TVC), total coliform count (TCC) and total staphylococcal count (TSC). Samples were inoculated into selective media Eosin Methylene Blue (EMB) agar, Salmonella Shigella (SS) agar, Thiosulphate Citrate Bile Salts Sucrose (TCBS) agar and Mannitol Salt (MS) agar. E. coli and Staphylococcus spp. were identified from the samples. The TVC in spicy puffed rice sample ranged from log 4.5 cfu/g to log 5.4 cfu/g, TSC ranged from log 4.4 cfu/g to log 5.2 cfu/g and TCC ranged from log 1.4 cfu/g to log 4.3 cfu/g. Antibiotic sensitivity test showed that the isolates were sensitive to ciprofloxacin and gentamicin. E. coli were resistant to ampicillin, chloramphenicol and cephalexin and Staphylococcus spp. were resistant to ampicillin, cephalexin and vancomycin. Spicy puffed rice sold by the street vendors at BAU campus harboured multidrug resistant food borne bacteria which may cause public health hazard. DOI: http://dx.doi.org/10.3329/bvet.v31i1.22839 Bangl. vet. 2014. Vol. 31, No. 1, 20-26